2007
DOI: 10.1016/j.ygyno.2006.10.044
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with return for routine annual screening in an ovarian cancer screening program

Abstract: Objective-To identify clinical, demographic, dispositional and attitudinal variables associated with return for routine, annual transvaginal sonography (TVS) screening for ovarian cancer.Methods-Asymptomatic, average to high risk, women (n=585) participating in a free universitybased ovarian cancer screening program completed a baseline interview prior to undergoing an initial TVS screening test. During the baseline interview, demographic (age, education, partner status, race), clinical (family history of ovar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 32 publications
1
7
0
Order By: Relevance
“…Screening attendance was additionally related to education and vocational training consistent to other national (ScheVer et al 2006) and international results reported from Australia (Taylor et al 2001) and the USA (Coughlin et al 2006;Andrykowski et al 2007) showing higher attendance among women with better education or vocational training. (1991)(1992)(1993)(1994)(1995)(1996)(1997)(1998)(1999)(2000)(2001)(2002)(2003)(2004)(2005) Again, in accordance to other national data (ScheVer et al 2006), no clear association of screening attendance with employment status was found, but occupational position was associated with screening.…”
Section: Discussionsupporting
confidence: 83%
“…Screening attendance was additionally related to education and vocational training consistent to other national (ScheVer et al 2006) and international results reported from Australia (Taylor et al 2001) and the USA (Coughlin et al 2006;Andrykowski et al 2007) showing higher attendance among women with better education or vocational training. (1991)(1992)(1993)(1994)(1995)(1996)(1997)(1998)(1999)(2000)(2001)(2002)(2003)(2004)(2005) Again, in accordance to other national data (ScheVer et al 2006), no clear association of screening attendance with employment status was found, but occupational position was associated with screening.…”
Section: Discussionsupporting
confidence: 83%
“…Some social characteristics such as low education are risk factors in ovarian cancer and breast cancer screening [24,25] . Occupation tended to be a risk factor that affected the screening rate more for men than for women.…”
Section: Discussionmentioning
confidence: 99%
“…Participants indicated their extent of agreement with two statements: ''A Transvaginal Sonography screening test can find ovarian cancer early'' and ''Ovarian cancer can be cured if found early'' (Andrykowski et al, 2007). Responses were recorded on identical 4-point Likert scales ranging from (1) ''Strongly Disagree'' to (4) ''Strongly Agree.''…”
Section: Cancer Screening Beliefsmentioning
confidence: 99%